Writing A Research Paper: A Guide - Shrestha, Laxmi; Joshi, Bishal; Kumar, Anand (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION A research paper is a part of academic writing where there is a gathering of information from different sources. It is multistep process. Selection of title is the most important part of research writing. The title which is interesting should be chosen for the research purpose. All the related information is gathered and the title for research is synthesized. After thorough understanding and developing the title, the preliminary outline is made which maintains the logical path for its exploration. After preliminary research, proper research work is started with collection of previous resources which is then organized and important points are noted. Then research paper is written by referring to outlines, notes, articles, journals and books. The research paper should be well structured containing core parts like introduction, material and methods, results and disscussion and important additional parts like title, abstract, references.